Oral contraceptive pills in the management of clomiphene resistant anovulation - Sangam Kumari; Nishi Mitra; Anita Singh (International Journal of Medical Research and Review, 2015)
Introduction: We tried to evaluate the effectiveness of 2 months oral contraceptive pill (OCP) pretreatment for clomiphene citrate (CC) resistant cases followed by repeat clomiphene citrate treatment.Material and Methods: In this study of 100 patients, 30 met the criteria of clomiphen citrate resistant anovulation . Before starting OCPs day 3 hormone profile assayed. All 30patients were given 2 months of continuous OCPs for hypothalamic –pituitary-ovarian axis suppression. After withdrawal bleeding, their day 3 hormonal profile assayed and clomiphene citrate was given from day 3-day7. Follicular growth monitored by sonography from day 12 till max size (>20mm) reached. 10,000 IU Hcg given to those patients who failed to show spontaneous rupture. Ovulation was confirmed by S. Progesterone assay on day 21. Pregnancy confirmed by S. Beta hCG level and 7 weeks amenorrhoea.Result: A total number of 30 patients completed 75 treatment cycles. 23 of them achieved ovulation. There were significant changes observed in hormonal profile in response to OCP treatment. 17 beta estradiol levels decreased to 58%, 63% reduction noted in LH level, androgen decreased by 56%. FSH level also decreased but not so significantly. 23 patients ovulated out of 30 patients (76.6%) which resulted in high ovulatory cycle 55/75 (73.2%) and Cumulative pregnancy rate 60% (18/30).Conclusion: This study showed the excellent ovulation and pregnancy rate following OCP suppression. This mode of treatment is a cheaper alternative to GnRH therapy for poor anovulatory women.